Pemanfaatan Pekarangan sebagai Upaya Peningkatan Ketahanan Pangan - Aliefman Hakim; Ellend Putri Kurnia; Nurul Lasmini; Ade Nusa Putra Dinata; Idmayanti Idmayanti; Irawanti Irawanti; Rosida Rosida; Rosmini Rosmini; Nurul Sakina (Jurnal Pengabdian Masyarakat Sains Indonesia, 2021)
Telaga Baru A is one of the area located in Telaga Bertong Village, Taliwang District, West Sumbawa Regency, West Nusa Tenggara Province, which had not used the house yard to improve the community's economy and national food security. One of the applicable steps that can be applied to optimize the yards of residents is the "Sustainable Food Homes" program. The Sustainable Food House program was a program of community service and empowerment in the local village in optimizing the house yard by planting organic vegetable seeds using the verticulture method. The verticulture method was a technique of cultivating plants vertically, so that planting was carried out in stages. The stages of the verticulture method were preparation of tools and materials, seeding, filling the soil in polybags, transferring seeds, and monitoring which was carried out in the morning and during the day. The vegetable seeds used include cabbage seeds, mustard greens, chilies, lettuce, celery, purple eggplant, fresh eggplant, water spinach, onions and spinach. To support plant growth and productivity, composting and application of compost to plant seeds was also carried out in this service activity. The result of implementing the Sustainable Food House and making compost was the improvement of the skills of the local people, so they were able to continue the program with village officials and achieve the goals they want to achieve.Keywords: Vegetable Seeds, Home Yard, Compost, Verticulture